Pengaruh Perendaman Cetakan Alginat Kedalam Air Seduhan Daun Sirih Merah (Pipper Crocatum) 25% Sebagai Bahan Desinfektan Terhadap Perubahan Dimensi Cetakan Alginat - Basri, Ira Setia Rahmi, drg. Noor Hafida Widyastuti, Sp.KG, drg. Nilasary Rochmanita S, MDSc (2015)
Dimensional change of alginate impression material was happened frequently due to imbibitions or absorption of disinfectant solutioninto impression material when it was submerged. Disinfectant solution that could be use as an alternative for dentistry was 25% steeping water of red betel leaf (piper crocatum). This study was conducted to find out the effect of alginate impression submersion into 25% red betel leaf (piper crocatum) steeping water as disinfectant material towards dimensional change of alginate impression. Research subjects were 32 divided into two treatment groups. Obtained data consist of data before and after impression submersion into 25% steeping water of red betel leaf (piper crocatum). When it was put on normality test, the result showed non normal distribution, so it wasn't qualified to deal with parametric test. Therefore, nonparametric test was applied with 95% significance level. The study showed significant dimensional change with p value p=0.000 (p<0.05). It could be concluded that there was an effect of alginate impression submersion into 25% red betel leaf (piper crocatum) steeping water as disinfectant material towardsdimensional change of impression.